Trait Association and Path Analysis Studies of Yield Attributing Traits in Rice (Oryza sativa L.) Germplasm - Gupta, Sneha; Upadhyay, Sameer; Koli, Ganesh Kumar; Rathi, Sanket Rajendra; Bisen, Prashant; Loitongbam, Bapsila; Singh, Pawan Kumar; Sinha, Brajesh (International Journal of Bio-resource and Stress Management, 2020)
Forty-eight Rice germplasm were undertaken for estimating variability, heritability, genetic advance, correlation and path analysis for yield and yield attributing traits. The experiments were conducted in a randomized block design with three replications during two-season viz., July-Oct, 2017 and July-Oct, 2018 at the Agriculture Research Farm, Institute of Agricultural Sciences, Banaras Hindu University Varanasi. Analysis of variance revealed that genotypes contain significant differences for all the traits. High estimates of GCV and PCV were observed for traits like filled grains panicle-1 followed by total grains panicle-1, grain yield plant-1 and number of effective tillers plant-1. High heritability coupled with high genetic advance as % of mean was observed for the traits viz. plant height, days to 50% flowering and test weight. These characters exhibited less influence of environmental variance in their inheritance and hence could be improved by means of simple selection. Path analysis revealed that characters like filled grains panicle-1, total grains panicle-1 and number of effective tillers plant-1 had prominent direct positive effects on grain yield plant-1. Genotypes LC-53, LC-55 and LC-50 and LC-59 were found to be superior for yield and contributing traits during July-Oct, 2017 and July-Oct, 2018 respectively while LC-90 was found to be consistently overling under both seasons. Genotypes LC-54 and LC-56 were earliest in flowering and maturity suggesting that they can be used as a donor in hybridization programme for evolving early maturing rice variety.